Hydrophobic Aerogel-Based Film Coating On Glass By Using Microwave - Poerwadi Bambang; Diah Agustina P; Christia Meidiana (UNEJ e-Proceeding, 2016)
Naturally hydrophobic films is currently receiving a lot of attention and has inspired efforts to create biomimetic surfaces. Application technology can be used as a water repellent coatings, for glass at a solar cell that can clean independently, so the use of outdoor solar cell can be used in a relative long period of time. In this study, the silica sol is made by making a solution of Na Silicate at 7%. and for the stabilization solution is used 1 M citric acid solution until a pH of about 2. Glass hydrophobic obtained by film coating on the glass test by means of dip coating, silica sol used is stabilized silica sol, glass coated silica sol are soaked in a surface-modifying agent that is TEOS, methanol, and n hexane in the ratio 1: 1: 1 volume ratio. The goal of treatment is to form silanol groups on the silica surface. The best hydrophobicity properties obtained on condition of Na silicate 7%, the modification time 2 hours at a temperature of 300C, the contact angle (Ө) of 128.40. The results of the study when compared to heating without microwave which takes 7 hours at 500C in terms of aspects of energy consumption, the use of the microwave can save energy by almost 85% to earn hydrophobic movie characters.